How istanbul HSBC bank operators use lotus notes within electronic performance support systems - (:unkn) unknown (My University, 2006)
From the educational and training point of view, to understand and use the Electronic Performance Support Systems (EPSS) efficiently is important in developing web-based applications. In this way, the aim of the study is proving the idea that Lotus Notes is a convenient tool for creating a powerful EPSS within the HSBC Bank example in Istanbul. For this reason, EPSS Domain Features Checklist is developed to assess the study group's perceptions at the bank. The participants of the present study group consisted of 104 expert Lotus Notes (LN) users from the Bank Executive Management Center in Istanbul. The study group was asked online to rank the LN program for the bank applications within the EPSS Domain Features Checklist. Based on the checklist data, the experts' (HSBC Bank operators') perceptions on the LN were calculated within the EPSS features. The study showed that LN is a suitable tool for creating powerful EPSS activities within the HSBC Bank example.
Keywords: Domains; EPSS; Features; HSBC Bank; Lotus Notes; Training and Education